A study of atmosphere perception of dynamic coloured light. (December 2014) - Wang, HH; Luo, M Ronnier; Liu, P; Yang, Y; Zheng, Z; Liu, X
A psychophysical experiment has been carried out to investigate the impact of dynamic lighting parameters on atmosphere perception. The experiment was conducted in a purpose-built LED lighting lab, where the lighting could be spatially and dynamically changed and colorimetric specifications controlled. The aim of this study was to investigate the impacts of speed, saturation and brightness of dynamic lighting on the perceived atmosphere, preference and suitability for certain spaces. Twenty native Chinese observers participated in the experiment, each assessing the environment under dynamic lighting conditions using 21 atmosphere terms. The results show significant gender differences on some scales such as safe, spatial, chilly, formal, preference and office-like. Factor analysis showed that the 21 scales can be grouped into three categories: tenseness, coziness and liveliness, and that a living room-like atmosphere evaluation is consistent with coziness. Dynamic lighting does have a significant influence on atmosphere perception. A more saturated LED light would lead to less tense, more cosy, more safe and more lively atmosphere perceptions. By increasing the speed, a more tense and less cosy atmosphere can be generated. Medium speed offers the most lively and preferred atmosphere. Brighter lighting will generate a less tense environment. More saturated colour and a slower speed will produce a more living room-like environment, but it seems that such dynamic lighting is not suitable for an office-like environment.